E-LEARNING IMPLEMENTATION IN RURAL AREA: THAILAND PRIMARY SCHOOL EFL PERCEPTION - Adinda Tasya Aulia Octaviani Prayudi Daulay; Khoirul Anwar (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
This study aimed to find primary school EFL perception in Loei on E-learning during the Covid-19 outbreak. This study is using descriptive quantitative design using questionnaire as the instrument and involving 125 primary school EFL from 6 different districts in Loei, Thailand. To find valid answer, Gutmann scale has been applied in this study consisting of 4 aspects namely interactivity, independency, accessibility and enrichment. The results show that the mean score is 8.34 (min score: 3 & max score: 12) and the standard deviation is 2.152. Thus, it can be said that EFL perceptions in Loei, Thailand primary school on E-learning implementation is fairly good. The findings of this study are to assist English teachers making it possible to design more effective E-learning implementation during the outbreak mainly for EFL in rural areas.